Chinese Life in Colonial Indonesia (Part.1) : the Kong Koan Archives 1909-1920 - Erkelens, Monique,; Hoogervorst, Tom G., (Asian Studies E-Books Online, Collection 2025., 2025)
During the colonial and early independence periods, the Chinese community in Batavia/Jakarta was governed by the semi-autonomous Kong Koan (Chinese Council). Its members, known as Chinese officers, regularly convened to discuss civil registration, taxation, religion, finances, health, education, safety, legal matters, and other community concerns. This volume presents the Council's annotated Malay minutes: unique archival material that provides insights into the daily life of Indonesia's vibrant Chinese-descended community. While much existing scholarship relies on Dutch sources, this volume offers a perspective from within. See Less